Design of Comb-Line Array Antenna for Low Sidelobe Level in Millimeter-Wave Band - Jae-Ho Lee; Sang-Hoon Lee; Hyun Joon Lee; Jung-Hoon Oh; Jang-Yeol Kim; In-Kui Cho; Dong-Wook Seo (IEEE Access, 2022)
In this paper, a deformed radiating element is proposed to design a comb-line array antenna for low sidelobe levels in the millimeter-wave band. To design the comb-line array antenna with a low sidelobe level, the use of the wide radiating elements for a relatively large radiation conductance is required. However, the conventional rectangular radiating element has transverse current flows on it, resulting in undesirable transverse radiation conductance for cross-polarization. On the contrary, in the proposed radiating element, which is implemented by cutting obliquely the connection part to the feeding line from a rectangular element, the radiations from the transverse currents cancel each other, and low radiation conductance for cross-polarization and dominant radiation conductance for co-polarization are achieved. A 17-element linear comb-line array antenna with the sidelobe below −20 dB is designed and measured at 79 GHz. Using the proposed radiating elements, we obtained the sidelobe level of −21.9 dB in the array, but the array using the conventional radiating elements shows the sidelobe level of −16.9 dB. This letter demonstrates the availability of the proposed element for the easy and accurate design of the comb-line array antenna with the low sidelobe level.